Spasmolytic and Antinociceptive Activities of Ursolic Acid and Acacetin Identified in Agastache mexicana - González-Trujano, María Eva; Ventura-Martínez, Rosa; Chávez, Marco; Díaz-Reval, Irene; Pellicer, Francisco (Planta Medica, 2012)
Agastache mexicana is a plant in high demand that has long been used in Mexican folk medicine to treat anxiety, insomnia, and stomachache, among other afflictions. Ursolic acid and acacetin were isolated and identified as two possible active compounds of A. mexicana aerial parts. An antinociceptive response was demonstrated in a significant and dose-dependent manner with ursolic acid and acacetin (i. p. and p. o.) in comparison to the analgesic diclofenac by using the writhing test in mice. Moreover, acacetin also produced a significant concentration-dependent spasmolytic response with major efficacy compared to ursolic acid and papaverine by using rings from the isolated guinea pig ileum. These results provide evidence of the presence of two active constituents of Agastache mexicana reinforcing its utility as a therapy for visceral pain as used in traditional medicine.
Keywords: acacetin; Agastache mexicana (H. N. K.) Lint & Epling subsp. xolocotziana; Lamiaceae; antinociception; spasmolytic; ursolic acid